A closer look to neural pathways and psychopharmacology of obsessive compulsive disorder - Gargano, Steven P.; Santos, Melody G.; Taylor, Sydney M.; Pastis, Irene (Frontiers in Behavioral Neuroscience, 2023)
The intricate neural pathways involved in obsessive-compulsive disorder (OCD) affect areas of our brain that control executive functioning, organization, and planning. OCD is a chronic condition that can be debilitating, afflicting millions of people worldwide. The lifetime prevalence of OCD in the US is 2.3% (Obsessive-Compulsive Disorder (OCD), 2017). OCD is predominantly characterized by obsessions consisting of intrusive and unwanted thoughts, often with impulses that are strongly associated with anxiety. Compulsions with OCD encompass repetitive behaviors or mental acts to satisfy their afflicted obsessions or impulses (Stein et al., 2019). While these factors can be unique to each individual, it has been widely established that the etiology of OCD is complex as it relates to neuronal pathways, psychopharmacology, and brain chemistry involved and warrants further exploration.